Physico-chemical Studies of Cobalt(II) Complexes Derived from 2-Substituted Benzaldehyde Semicarbazones and Thiosemicarbazones - Kumar, Brajesh; Sangal, S.K.; Kumar, Arun (Asian Journal of Chemistry, 2010)
Cobalt(II) complexes with 2-chlorobenzaldehyde/2-ethoxybenzaldehyde semicarbazone and thiosemicarbazone (cbsc, cbtsc, ebsc and ebtsc) have been synthesized and characterized by means of various physico-chemical techniques viz., elemental analysis, magnetic moment, infrared spectral and electronic spectral studies. IR spectral studies showed bidentate chelating behaviour of the ligands coordinating through azomethine nitrogen and carbonyl oxygen/thioketo sulphur atoms. Magnetic moment of these complexes indicates high spin configuration. The probable structure for all the metal complexes is also proposed here.